Effect of Tempo on Temporal Expectation Driven by Rhythms in Dual-Task Performance - Xu, Zhihan; Ren, Yanna; Misaki, Yosuke; Wu, Qiong; Lu, Sa (Frontiers in Psychology, 2021)
Temporal expectation is the ability to focus attention at a particular moment in time to optimize performance, which has been shown can be driven by regular rhythms. However, whether rhythm-based temporal expectations rely upon automatic processing or require the involvement of controlled processing has not been clearly established. Furthermore, whether the mechanism is affected by tempo remains unknown. To investigate this research question, the present study used a dual-task procedure. In the single-task, participants were instructed to respond to a visual target preceded by a regular or an irregular visual rhythm under a fast (500 ms) or slow (3500 ms) tempo. The dual-task simultaneously combined a working memory (WM) task. The results showed temporal expectation effects in which participants responded faster to the regular than to the irregular conditions in the single-task. Moreover, this effect persisted under dual-task interference in the fast tempo condition but was impaired in the slow tempo condition. These results revealed that rhythmic temporal expectation induced by fast tempo was dependent on automatic processing. However, compared to the faster tempo, temporal expectation driven by a slower tempo might involve more controlled processing.